Circulating tumor cells in different stages of colorectal cancer - Eliasova, Petra; Pinkas, Michael; Kolostova, Katarina; Gurlich, Robert; Bobek, Vladimir (Folia histochemica et cytobiologica, 2017)
INTRODUCTION: Liquid biopsies are noninvasive tests using blood or body fluids to detect circulating tumor cells (CTCs) or the products of tumor cells, such as fragments of nucleic acids or proteins that are shed into biological fluids from primary tumor or its metastates. The analysis of published clinical studies provides coherent evidence that the presence of CTCs detected in peripheral blood is a strong prognostic factor in patients with colorectal carcinoma (CRC). The aim of the study was to implement size-based separation protocol of CTCs in CRC patients. MATERIAL AND METHODS: Patients diagnosed with different stages of CRC (n = 98) were included in the study. All patients have been diagnosed for colorectal adenocarcinoma by pathology examination, 45 patients with colon carcinoma and 53 with rectosigmoid cancer. A size-based separation method (MetaCell®) for viable CTC enrichment from peripheral blood was used to assess the presence of CTCs by cytomorphological evaluation using vital fluorescence microscopy. RESULTS: Cytomorphological analysis revealed that 81 (83%) tested samples were CTC-positive and 17 (17%) were CTC-negative. We report a successful isolation of CTCs with proliferation potential in patients with CRC. The CTCs were cultured in vitro for further downstream applications. Some of the isolated CTCs were able to grow in vitro for 6 months as a standard cell culture. CONCLUSIONS: We established a reliable, inexpensive and relatively fast protocol for CTCs enrichment in CRC patients by means of vital fluorescence staining which enables their further analysis in vitro.
Keywords: senioři; fluorescenční mikroskopie; senioři nad 80 let; MetaCell®; Microscopy, Fluorescence; kolorektální nádory; cell culture; nádorové cirkulující buňky; Middle Aged; Colorectal Neoplasms; mužské pohlaví; adenokarcinom; Tumor Cells, Cultured; Aged, 80 and over; ženské pohlaví; Humans; staging; lidé středního věku; circulating tumor cells; rectosigmoid cancer; Female; Aged; colon cancer; nádorové buňky kultivované; Neoplastic Cells, Circulating; Adenocarcinoma; lidé; Male